An empirical study of the factors influencing information disclosure behaviour in social networking sites - Salleh, Norsaremah; Hussein, Ramlah; Mohamed, Norshidah; Aditiawarman, Umar (2013)
Since the introduction of social networks over a decade ago, a number of research has focused on understanding the behavior of social network user in disclosing information over the Social Network Sites(SNS). Although the issue of privacy breach on SNS has been widely reported, very few studies have used the Protection Motivation Theory (PMT) as a framework to understand SNS user’s behaviour related to information disclosure. This study employed the PMT, incorporated with trust, perceived risk and privacy concern to investigate the factors affecting information disclosure behavior on SNS among 486 undergraduate students in Malaysia. Our findings showed that perceived risk, perceived benefits and trust on SNS influenced individual information disclosure behaviour. However, privacy concern was found not related to information disclosure behaviour.